ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN ENERGI LISTRIK PT. PLN DI KALIMANTAN BARAT TAHUN 2012-2020 - Rio Hamdan Prihastama; Muhammad Arif (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Electricity is an important need for people in all regions of Indonesia in this era. The purpose of this study was to determine the effect of population, economic growth, foreign investment, domestic investment, and the construction cost index on electricity sales in all cities or districts in West Kalimantan Province. The data used in this study are secondary data in the form of time series and cross-section data sourced from the Central Bureau of Statistics and the Dukcapil of West Kalimantan Province in 2012-2020. The method used in this research is panel data analysis method.